Naturalistic Study on Communication StrategiesUsed by Sixth Semester Students in Microteaching Class of English EducationDepartment of Muhammadiyah University of Surakarta - Hikmah, Nurul, Prof. Dr. Endang Fauziati, M.Hum, Hepy Adityarini, Ph.D (2016)
This study was descriptive qualitative study concerning with Communication Strategies. The objectives of this study were to identify the types of Communication Strategies and to identify the dominant types of Communication Strategies. The data of research were communication strategies used by sixth semester students in Microteaching class of English Education Department of Muhammadiyah University of Surakarta in 2015/2016 academic year. There was one source of data used in this research, namely: event. In this study only involved 1 class of Microteaching consisting17 students as the subject of the research. The technique of collecting data in this study was indirect observation. The data were analyzed based on Celce-Murcia taxonomy of communication strategies. The result of this study showed that there were five types with twelfth sub-types of communication strategies used by the students conducting teaching practice in Microteaching class, these being; Avoidance or Reduction Strategies (Topic Avoidance and Message Abandonment), Achievement or Compensatory Strategies (Circumlocution, Approximation, Non-linguistic Means, Restructuring, Word Coinage and Retrieval), Stalling or Time-gaining Strategies (Filler, Hesitation and Self and Other Repetition), Self-monitoring Strategies (Self-initiated Repair), and Interactional Strategies (Repetition Request). The most dominant types of communication strategies used by students was Stalling or Time-gaining Strategies and the least frequent type of communication strategies used by students was Avoidance Reduction Strategies. These results implied that the students need to improve their ability in mastering vocabulary and speaking skills.